Efektivitas Penerapan Aplikasi SMART ASN di Kantor Kementerian Agama Kabupaten Bungo - Wiwoho, Raino; Diana, Fera (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This article aims to determine the effectivness of using SMART ASN Application in order to improve the monitoring of employees discipline in The Office of Ministry of Religion of Bungo Regency. The method used in this study is quantitative with descriptive approach through primary data was obtained by interview. Based on the identification of 15 respondents to the three indicators of effectiveness, goal attainment, integration, and adaptation, it is known that the implication of ASN SMART Application in increasing supervision of the discipline of the employees of The Office of Ministry of Religious Affairs of Bungo Regency has been carried out well but because there are still several obstacles in its application, it can be assessed as less effective. The obstacle is when the application cannot be accessed so employees must report their presence to human resources field and do the manual report. Keywords: Effectivness, SMART ASN Application, Monitoring, Discipline